2019
DOI: 10.1177/1420326x19891225
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study monitoring the thermal comfort of the elderly living in nursing homes in Hefei, China, using wireless sensor networks, site measurements and a survey

Abstract: Due to the rapid growth of the ageing population and the shrinking of family size in China, there has been a steady increase in the demand for nursing homes. The Chinese government has encouraged the development of nursing homes. However, there is no clear understanding of the thermal environment of nursing homes and the thermal comfort of their residents. Therefore, this paper describes a pilot study that was undertaken to investigate the thermal comfort of senior residents living in nursing homes. A wireless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Besides, the thermal environment is an important factor that could affect sleep quality. [18][19][20][21] Therefore, the objective of this study is to carry out more detailed unsteady thermal comfortable research on the sleeping environment during defrosting, in aspects of airflow and temperature distribution and thermal comfort distribution. In this study, considering the advantages of energy saving of task/ambient air conditioning (TAC) system, 22,23 a task/ambient ASHP (T-ASHP) system was designed, which can deliver the heated air from the ASHP directly to the sleeping human body.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the thermal environment is an important factor that could affect sleep quality. [18][19][20][21] Therefore, the objective of this study is to carry out more detailed unsteady thermal comfortable research on the sleeping environment during defrosting, in aspects of airflow and temperature distribution and thermal comfort distribution. In this study, considering the advantages of energy saving of task/ambient air conditioning (TAC) system, 22,23 a task/ambient ASHP (T-ASHP) system was designed, which can deliver the heated air from the ASHP directly to the sleeping human body.…”
Section: Introductionmentioning
confidence: 99%
“…Through the recent advancements in multiple algorithms and technologies, wireless sensor nodes are equipped with sensing, processing, computing, and communicating capabilities [9]. Besides, due to features such as cognitive performance, low cost, and high fault tolerance, the vision of the WSNs is couched on many applications, including traffic control systems [10][11][12], biomedical health monitoring [13,14], automated assistance for the elderly [15,16], industrial control systems [17], virtual reality [18][19][20], and environmental monitoring systems [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…20 A recent study on elderly thermal comfort in a nursing home in China found considerable adaptive behaviours in response to seasonal variations of thermal environments. 21 To many elderlies, the use of open spaces during hot period is considered a heat-coping strategy, 22 and the behaviour was often formulated prior to the advent of home air conditioning. 23 Physiologically, the elderlies are considered the most vulnerable group under heat stress, due to reduced thermoregulatory responses such as sweating rate, skin blood flow and cardiovascular functions.…”
Section: Introductionmentioning
confidence: 99%